The Interface Friction in The Friction-Type Bolted Joint of Steel Truss Bridge: Case Study - Gaoxin Wang; Youliang Ding (The Baltic Journal of Road and Bridge Engineering, 2020)
The friction-type bolted joint transfers the internal forces in the structural members by interface friction, but noticeable seasonal temperature and bolt fracture cause the redistribution of interface friction and threaten the joint safety. Therefore, this study carried out finite element analysis on the interface friction considering the influence of seasonal temperature and bolt fracture. Through finite element analysis, the simulation of interface friction under seasonal temperature revealed the distribution of temperature induced interface friction in different areas and locations. Further simulation of fractured bolts revealed the influence of quantity and location of fractured bolts on the redistribution of interface friction. Finally, the interface frictions in the bolted joint were evaluated using limit state equations. The results showed that: 1) the quantity and location of fractured bolts cause obvious redistribution of interface friction in the bolt-fractured areas; 2) the quantity and location of fractured bolts have slight effect on the total interface friction in the whole splice plate; 3) the reduced interface friction in the bolt-fractured areas was transferred to the areas without bolt fracture, producing little change in the total interface friction; 4) all the splice plates had abundant safety margin after analysis of their limit state equations.